Pelatihan Pembuatan Insektarium di SMA N 2 Muaro Jambi - Siburian, Jodion; Yusuf, Muhammad; Sadikin, Ali; Mursyd, Danial; Astriawati, Fitri (Journal of Community Engagement Research for Sustainability, 2023)
Abstract Insektarium is one of the solutions in overcoming the limitations of learning activities in the classroom. Through insektarium teachers and students can learn information about insects. This service aims to carry out training in making insektariums at SMA N 2 Muaro Jambi. The methods used include material delivery, discussion, and practice. The results showed that the training participants were able to make an insektarium by following the work procedures that had been explained. Thus, the service activities have fulfilled the objectives and achieved the required solutions. It is hoped that activities like this will be carried out in other places, as an effort to maximize learning in the classroom.